EVALUATION OF MANAGEMENT OF THE LUNG TB PROGRAM WITH DOTS STRATEGY IN THE WORK AREA OF COAL DISTRICT HEALTH DEPARTMENT DURING THE COVID-19 PANDEMIC - Widiyana .; Harris Rambey (JURNAL KESMAS DAN GIZI (JKG), 2022)
DOTS is a strategy to tackle tuberculosis. The COVID-19 pandemic has caused impacts on various aspects of life, including health. Batubara Recency in 2019, the percentage of case findings was 38.9% to 38% in 2020, and the rate of successful treatment decreased from 91.6% to 83.59%. This study aims to evaluate the management of the Pulmonary Tuberculosis program with 3 DOTS strategies in the Batubara District Health Office work area during the COVID-19 pandemic. This type of research is quantitative with an analytic survey method and a cross-sectional study approach. The sample consisted of TB program holders and laboratory staff at the Community Health Centre (Puskesmas) in Batubara District Health Office, totaling 32 respondents. Data analysis using chi-square test. The results showed that microscopic sputum examination/TCM was carried out quite well by 11 (64.7%) laboratory staff respondents. It was related to several Puskesmas that did not yet have microscopes, and during the COVID-19 pandemic, the workload of laboratory officers was high with many COVID-19 samples. In contrast, the number of laboratory officers at each Puskesmas was mainly only one person. TB treatment with OAT supervised by PMO has been implemented quite well by 11 (73.3%) TB officer respondents. It is related to the change of TB officers so that education of patients and PMOs is only once at the beginning of treatment. As a result, PMOs are negligent in carrying out their duties. At the same time, the availability of OAT has been implemented properly by 12 (80.0%) TB officer respondents. The availability of OAT is not optimal because there is a change in the OAT collection system, so there is no coordination between TB officers and pharmacists. There is no drug stock card at the Puskesmas, so the availability of OAT stock cannot be monitored monthly. Tuberculosis management with the DOTS strategy has not been maximized, so the Batubara Regency Health Office conducts advocacy to local governments and supervises health centers on molecular rapid test kits (TCM) so that all Puskesmas can become Microscopic Referral Community Health Center (PRM).